MECHANISTIC STUDY OF PHOTOELECTROCHEMICAL REACTIONS - PHOTOTRANSIENT EXPERIMENTS - Compton, R; Dryfe, R; Hirst, J (1994)
A novel channel electrode phototransient experiment for the mechanistic study of photoelectrochemical reactions is described in which the evolution of the photocurrent in time is monitored after the stepwise application of light to the system once steady-state transport-limited currents have been established in the dark. It is shown that the phototransient data in combination with steady-state photocurrent/flow rate data can accomplish mechanistic discriminations which may be impossible using the latter data alone. The theory of the experiment is given and a working surface presented which allows the analysis of experimental transients regardless of the cell geometry or solution flow rate used in their measurement. The approach is applied to the photoelectrochemical reduction of p-bromonitrobenzene in acetonitrile solution at a platinum electrode. The process, in the presence of light of wavelengths near 330 nm, is shown to be of the photo-ECE type. © 1994 American Chemical Society.